An Analysis of Influential Factors on Tourism Destinations Competitiveness - KALEJI, Lotfali KOZEGAR; HESAM, Mehdi; KAZEMI, Mohammad (Journal of Environmental Management and Tourism, 2017)
Tourism destinations of physical environment include tourism products such as support services, tourist attractions, and tourism resources, which are available in various scales. These locations are in active competition to raise tourism rate of income. This research uses a model suggesting that destination competition should be evaluated not only by its potential in improving life style and social development, but also through proficiency in resource allocation resulting in long-term economic prosperity. Accordingly, the present study for the first time seeks to analyze the influential factors on the tourism destinations competitiveness in Anzali Special Economic Zone. Required data obtained by a 36-item questionnaire through which the views of 40 tourism experts and specialists selected from Gillan Province Cultural Heritage, Handicraft and Tourism Organization as well as Gillan University. To determine the influential factors, the Factor Analysis Tests were used, while Friedman test was applied to prioritize the effect of components in tourism destination competitive advantage of Anzali Special Economic Zone. The results of this study revealed a crucial importance of tourism attractions and planning components